Domestic waste management planning at PLN (PERSERO) UPK Lombok ULPLTD Paokmotong: 3R progrrm approach - Melinda, Tina; Wahyudin, Wahyudin; Juliartha, I Putu Eka (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
Effective and sustainable domestic waste management is essential for PT PLN (Persero) UPK Lombok ULPLTD Paokmotong. In facing environmental challenges and increasingly stringent regulatory demands, this company needs to carry out domestic waste management planning based on waste generation and composition. This study aimed to determine waste management planning with the 3R program at ULPLTD Paokmotong. The research method in this study is descriptive qualitative with data collection techniques: interview methods, surveys, and measurements of domestic waste generation and composition at PT PLN (Persero) UPK Lombok ULPLTD Paokmotong. The results of this study indicate that TPS 3R at ULPLTD Paokmotong serves 61 employees. Based on the type of waste, the proposed waste management strategy, namely implementing the 3R program at PT PLN (Persero) UPK Lombok ULPLTD Paokmotong, has proven effective in reducing waste generation and optimizing resource use. Through waste reduction efforts at the source, reuse of recyclable materials, and efficient recycling processes, companies can reduce environmental impacts and generate sustainable economic benefits. Based on the planning of waste containers that must be provided by ULPLTD Paokmotong of 3.14 liters, placed in each building and distinguished by the type of waste, namely organic, inorganic, and B3. With an organic waste volume of 18 L / day with a compostable waste capacity of 14.4 L / day. Meanwhile, in implementing the 3R program based on the calculation results, the total volume of composting produced is 540 L / month. The total number of composter drums that must be prepared is seven pieces. As for residual waste, it has a volume of 4 L / day with a container capacity of 28 L and an inorganic waste storage area of 2 m3 with a length of 2 m, width of 1 m, and height of 1 m. The suggestion in this study is that it is hoped that the next researcher will add the Draft Budget for the construction of TPS 3R and the DED of the TPS 3R building.